Literatos en 90 minutos. (Pack 2), (Tolstói, Poe, Virginia Woolf, Dostoievski, D.H. Lawrence y Kafka) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Literatos 2 collection brings together 6 of the most outstanding writers of the late nineteenth and early twentieth centuries.
Tolstói en 90 minutos -- Poe en 90 minutos -- Virginia Woolf en 90 minutos -- Dostoievski en 90 minutos -- D.H. Lawrence en 90 minutos -- Kafka en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Tolstoy, Leo, -- graf, -- 1828-1910.; Poe, Edgar Allan, -- 1809-1849.; Woolf, Virginia, -- 1882-1941.; Dostoyevsky, Fyodor, -- 1821-1881.; Kafka, Franz, -- 1883-1924.; Lawrence, D. H. -- 1885-1930.; Biographies; Electronic books